Survey on cellular phone usage on students in Thailand - Naohito Kawasaki (2018)
The number of cellular phone subscribers is increasing every year and there have been reports of health disorders related to the high-frequency radio waves. This paper considers the dependence of Thai university and high school students on cellular phones. A survey form (cellular phone dependence questionnaire: CPDQ) was distributed to 181 female and 177 male Thai university students and to 240 female and 140 male Thai high school students. The surveys were collected, Cronbach α coefficient was calculated, and a factor analysis was performed using the principal factor method and varimax rotation. The total scores were 16.54 to 20.04 and the Cronbach's α coefficients were 0.808 to 0.930. According to a factor analysis of 20 scored items, 4 factors were extracted for both male and female high school students, and the cumulative correlation coefficients of the male and female groups were 64.85% and 62.70%, respectively. Five factors were extracted for male university students and 6 factors were extracted for female university students, and the cumulative correlation coefficients were 58.08% and 57.91%, respectively. The W value results of the Shapiro-Wilk W-test for male university students, female university students, male high school students and female high school students were 0.969, 0.984, 0.964, and 0.913 respectively, thus verifying the normality of the score distributions. The total scores for the Thai university students were higher than the scores for the Thai high school students. The factor analysis of female high school students confirmed a large difference compared to male university students, male high school students, and Japanese female university students. (The Japanese students were surveyed in an earlier study by Toda et al.). Also, the CPDQ total score was high, which indicated a strong tendency toward dependence.